2008
DOI: 10.1021/es8006518
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Speciation of Arsenic-Accumulating Mineral in a Sedimentary Iron Deposit by Synchrotron Radiation Multiple X-ray Analytical Techniques

Abstract: The comprehensive characterization of As(V)-bearing iron minerals from the Gunma iron deposit, which were probably formed by biomineralization, was carried out by utilizing multiple synchrotron radiation (SR)-based analytical techniques at BL37XU at SPring-8. SR microbeam X-ray fluorescence (SR-mu-XRF) imaging showed a high level of arsenic accumulation in the iron ore as dots of ca. 20 microm. Based on SEM observations and SR X-ray powder diffraction (SR-XRD) analysis, it was found that arsenic is selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…P exists in scorodite by isomorphous substitution of PO 4 3− for AsO 4 3− or by simultaneous incorporation into the crystal lattice, and is mineralogically expressed as a solid solution of scorodite and strengite, though they form only a partial solid-solution series. No continuous solid solution is produced due to the size difference between AsO 4 3− and PO 4 3− [26]. The electron backscatter images also suggest such Table 1 Chemical analyses of the arsenopyrite weathering products in the Barruecopardo mine wastes (Scms, Sc sf , Sc cl and Sccry: scorodite microcrystalline massive, spherulitic, colloform and in crystals, and R-b ph: Red-blackish phases).…”
Section: Electron Microprobe Analysismentioning
confidence: 96%
“…P exists in scorodite by isomorphous substitution of PO 4 3− for AsO 4 3− or by simultaneous incorporation into the crystal lattice, and is mineralogically expressed as a solid solution of scorodite and strengite, though they form only a partial solid-solution series. No continuous solid solution is produced due to the size difference between AsO 4 3− and PO 4 3− [26]. The electron backscatter images also suggest such Table 1 Chemical analyses of the arsenopyrite weathering products in the Barruecopardo mine wastes (Scms, Sc sf , Sc cl and Sccry: scorodite microcrystalline massive, spherulitic, colloform and in crystals, and R-b ph: Red-blackish phases).…”
Section: Electron Microprobe Analysismentioning
confidence: 96%
“…A few grams of the soil were dispersed in a high purity resin (Eposet, Maruto Co., Ltd), glued onto a glass plate with a wax product, and polished with abrasive α-Al 2 O 3 paper. The epoxy-resin was selected in this study because it was reported to be inert for metal oxidation states (Manceau et al, 2004) and was often used in similar μ-XAFS studies (Reguer et al, 2005;Takahashi et al, 2007;Endo et al, 2008) for embedding natural samples. After polishing to a thickness of about 40 μm, the thin section was removed from the glass plate by dissolving the wax (Takahashi et al, 2007).…”
Section: Preparation Of Thin Section Sample For Natural Soil Samplesmentioning
confidence: 99%
“…1 ). (2) 1 0.00702 (7) 0.00716 (10) 0.00517 (10) 0.00873 (11) 0.00036 (6) 0.00017 (7) 0.00011 (5) P/As -0.08690 (6) 0.14892 (3) 0.18386 (4) 0.9777(16)/ 0.00612 (10) 0.00672 (16) 0.00423 (15) 0.00742 (16) -0.00039 (10) 0.00023 (11) 0.00026 (9) 0.0223 ( 0.0269 (7) 0.0266 (7) 0.0102 (5) 0.0005 (…”
Section: Characterization Of As-bearing Phosphosiderite By Sc-xrdmentioning
confidence: 99%
“…[14] Nevertheless, the most likely incorporation mechanism for As 5 + into phosphosiderite remains the homovalent substitution of P 5 + , a mechanism already investigated and demonstrated for strengite. [15] In comparison to heterovalent substitution reactions which rely on balance reactions (e. g., [16,17]), or the incorporation of structural clusters where whole parts of the host structure are replaced (e. g., [18]), homovalent substitutions are considered to be relatively simple. In our study, however, we show that even the homovalent substitution of P 5 + by As 5 + can be relatively complex and best described by a combination of long-and short-range order methods.…”
Section: Introductionmentioning
confidence: 99%